Re-writing translated literature in Turkish: the case of “equal stories” - UYANIK, GÖZDE BEGÜM (My University, 2023)
Equality is a concept which could be considered in various aspects within a society. With that being said, this concept is mostly taken account of in terms of gender equality, and it is traditionally as well as subconsciously rooted in the very early ages of human beings; as a result of the effect of societies’ shaping their members. In parallel with this, children’s stories and fairy tales contribute to the children’s perception of the world and the nature. Moreover, they contribute to their world view regarding the gender-specific social roles of the human beings. They also have an effect on the way children think as well as on their behaviour within the society they live in. That is why, stories can be used as a tool for imposing certain behaviours and/or thoughts – either ideologically – in children as young adults. This has also been the case in translated children’s literature, for works to be translated are chosen according to a set of social norms in a literary system (cf. Gideon Toury, 1978/1995; Itamar Even-Zohar, 1978/1990). Shared by societies throughout the world, classic children’s stories have the same aim as well. These stories could be used as tools to make children have good deeds or to designate gender-specific roles on them. In line with this, translated classic children’s stories have started to be re-written in Turkish context in recent years, resulting in \"Equal Stories\" project – a series of classic children’s stories re-written in Turkish language which holds the aim for reflecting equal social status of men and women. This project has aimed to put the concept of gender equality in children’s mindset by asserting the claim that equality is of vital importance, for equal participation of women in social development would mean sustainable development of societies and its members. This study examines \"Equal Stories\" by focusing on how child figure has been re-written and re-interpreted to reflect gender equality as is claimed. In this respect, the study deals with unveiling the ways how gender-balance has been formed for the sake of strengthening women roles in these stories by giving examples and by illustrating the strategies used in the series. Discussion will be formed around whether realization of the claim that gender equality has been presented in those stories as well as the possible effects of the asserted claim on children as target readers.
Keywords: Sosyal ve Beşeri Bilimler; Dil ve Edebiyat; Batı Dilleri ve Edebiyatları; Mütercim-Tercümanlık; İngilizce Mütercim-Tercümanlık; Social Sciences and Humanities; Philology; Western Languages and Literatures; Interpreting and Translating; English Interpreting and Translating; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; EDEBİYAT; EDEBİYAT, ALMAN, HOLLANDA, İSKANDİNAV; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; LITERATURE; LITERATURE, GERMAN, DUTCH, SCANDINAVIAN; Edebiyat ve Edebiyat Teorisi; Sosyal Bilimler ve Beşeri Bilimler; Literature and Literary Theory; Social Sciences & Humanities